MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c) -> f1(a, b, c) (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(a, b, c) with all transitions in problem 1, the following new transition is obtained: f0(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] We thus obtain the following problem: 2: T: (1, 2) f0(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] with all transitions in problem 2, the following new transition is obtained: f0(a, b, c) -> f1(e', f', f) [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 ] We thus obtain the following problem: 3: T: (1, 3) f0(a, b, c) -> f1(e', f', f) [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e', f', f) [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 ] with all transitions in problem 3, the following new transition is obtained: f0(a, b, c) -> f1(e'', f'', f') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 ] We thus obtain the following problem: 4: T: (1, 4) f0(a, b, c) -> f1(e'', f'', f') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'', f'', f') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 ] with all transitions in problem 4, the following new transition is obtained: f0(a, b, c) -> f1(e''', f''', f'') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 ] We thus obtain the following problem: 5: T: (1, 5) f0(a, b, c) -> f1(e''', f''', f'') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''', f''', f'') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 ] with all transitions in problem 5, the following new transition is obtained: f0(a, b, c) -> f1(e'''', f'''', f''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 ] We thus obtain the following problem: 6: T: (1, 6) f0(a, b, c) -> f1(e'''', f'''', f''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'''', f'''', f''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 ] with all transitions in problem 6, the following new transition is obtained: f0(a, b, c) -> f1(e''''', f''''', f'''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 ] We thus obtain the following problem: 7: T: (1, 7) f0(a, b, c) -> f1(e''''', f''''', f'''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''''', f''''', f'''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 ] with all transitions in problem 7, the following new transition is obtained: f0(a, b, c) -> f1(e'''''', f'''''', f''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 ] We thus obtain the following problem: 8: T: (1, 8) f0(a, b, c) -> f1(e'''''', f'''''', f''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'''''', f'''''', f''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 ] with all transitions in problem 8, the following new transition is obtained: f0(a, b, c) -> f1(e''''''', f''''''', f'''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 ] We thus obtain the following problem: 9: T: (1, 9) f0(a, b, c) -> f1(e''''''', f''''''', f'''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''''''', f''''''', f'''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 ] with all transitions in problem 9, the following new transition is obtained: f0(a, b, c) -> f1(e'''''''', f'''''''', f''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 ] We thus obtain the following problem: 10: T: (1, 10) f0(a, b, c) -> f1(e'''''''', f'''''''', f''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'''''''', f'''''''', f''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 ] with all transitions in problem 10, the following new transition is obtained: f0(a, b, c) -> f1(e''''''''', f''''''''', f'''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 ] We thus obtain the following problem: 11: T: (1, 11) f0(a, b, c) -> f1(e''''''''', f''''''''', f'''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''''''''', f''''''''', f'''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 ] with all transitions in problem 11, the following new transition is obtained: f0(a, b, c) -> f1(e'''''''''', f'''''''''', f''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 ] We thus obtain the following problem: 12: T: (1, 12) f0(a, b, c) -> f1(e'''''''''', f'''''''''', f''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'''''''''', f'''''''''', f''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 ] with all transitions in problem 12, the following new transition is obtained: f0(a, b, c) -> f1(e''''''''''', f''''''''''', f'''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 ] We thus obtain the following problem: 13: T: (1, 13) f0(a, b, c) -> f1(e''''''''''', f''''''''''', f'''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''''''''''', f''''''''''', f'''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 ] with all transitions in problem 13, the following new transition is obtained: f0(a, b, c) -> f1(e'''''''''''', f'''''''''''', f''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 ] We thus obtain the following problem: 14: T: (1, 14) f0(a, b, c) -> f1(e'''''''''''', f'''''''''''', f''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e'''''''''''', f'''''''''''', f''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 ] with all transitions in problem 14, the following new transition is obtained: f0(a, b, c) -> f1(e''''''''''''', f''''''''''''', f'''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 /\ e'''''''''''' >= 1 /\ d''''''''''''' >= 1 /\ f'''''''''''' = 0 ] We thus obtain the following problem: 15: T: (1, 15) f0(a, b, c) -> f1(e''''''''''''', f''''''''''''', f'''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 /\ e'''''''''''' >= 1 /\ d''''''''''''' >= 1 /\ f'''''''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f1(e''''''''''''', f''''''''''''', f'''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 /\ e'''''''''''' >= 1 /\ d''''''''''''' >= 1 /\ f'''''''''''' = 0 ] with all transitions in problem 15, the following new transition is obtained: f0(a, b, c) -> f1(e'''''''''''''', f'''''''''''''', f''''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 /\ e'''''''''''' >= 1 /\ d''''''''''''' >= 1 /\ f'''''''''''' = 0 /\ e''''''''''''' >= 1 /\ d'''''''''''''' >= 1 /\ f''''''''''''' = 0 ] We thus obtain the following problem: 16: T: (1, 16) f0(a, b, c) -> f1(e'''''''''''''', f'''''''''''''', f''''''''''''') [ a >= 1 /\ d >= 1 /\ b = 0 /\ e >= 1 /\ d' >= 1 /\ f = 0 /\ e' >= 1 /\ d'' >= 1 /\ f' = 0 /\ e'' >= 1 /\ d''' >= 1 /\ f'' = 0 /\ e''' >= 1 /\ d'''' >= 1 /\ f''' = 0 /\ e'''' >= 1 /\ d''''' >= 1 /\ f'''' = 0 /\ e''''' >= 1 /\ d'''''' >= 1 /\ f''''' = 0 /\ e'''''' >= 1 /\ d''''''' >= 1 /\ f'''''' = 0 /\ e''''''' >= 1 /\ d'''''''' >= 1 /\ f''''''' = 0 /\ e'''''''' >= 1 /\ d''''''''' >= 1 /\ f'''''''' = 0 /\ e''''''''' >= 1 /\ d'''''''''' >= 1 /\ f''''''''' = 0 /\ e'''''''''' >= 1 /\ d''''''''''' >= 1 /\ f'''''''''' = 0 /\ e''''''''''' >= 1 /\ d'''''''''''' >= 1 /\ f''''''''''' = 0 /\ e'''''''''''' >= 1 /\ d''''''''''''' >= 1 /\ f'''''''''''' = 0 /\ e''''''''''''' >= 1 /\ d'''''''''''''' >= 1 /\ f''''''''''''' = 0 ] (?, 1) f1(a, b, c) -> f1(e, f, b) [ a >= 1 /\ d >= 1 /\ b = 0 ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 1.214 sec (SMT: 1.107 sec)